Eksistensi dan Karakteristik Putusan Ultra Vires Dewan Kehormatan Penyelenggara Pemilu - Wibisena Caesario (Jurnal Hukum IUS QUIA IUSTUM, 2024)
The Decisions of the Honorary Council for Election Administration (DKPP) serves as a crucial instrument for the DKPP in determining violations of the Code of Ethics on Election Administration. However, in its development, DKPP Decisions were found to exceed their authority (ultra vires). Constitutional Court Decision No. 115/PHPU.D-XI/2013 stated that the DKPP Decision should be limited to violations of the  Code of Ethics on Election Administration and if the content of the decision is beyond the a quo realm, thus the DKPP Decision should be declared non-binding and must not be adhered to. Subsequently, it leads to the cancellation of the DKPP Decision as it is considered legally flawed. This study attempts to identify the existence and characteristics of the ultra vires Decisions of DKPP, considering the significant impact of the nature of the a quo decision through two problem formulations. First, how is the existence of the Honorary Council for Election Administration's ultra vires Decision? Second, what are the characteristics of theHonorary Council for Election Administration's ultra vires Decision? This is a normative legal research with a descriptive-qualitative analysis method. As the results, an ultra vires decision occurs when the DKPP issues a decision beyond the violation of the Code of Ethics on Election Administration according to the existing statutory regulations and falls within the authority of the KPU and Bawaslu. The author identifies 7 ultra vires  decisions of the DKPP. There are three characteristics of the DKPP ultra vires decisions, namely (1) the substance of the ultra vires decisions lies in the ruling; (2) the DKPP ultra vires decision poses a restorative justice paradigm; (3) the ultra vires decision encourages the Administrative Court to assess the binding force of the DKPP Decision and its follow-up decisions. The ruling of ultra vires decision  is also expressed differently, namely (1) in the form of a stand-alone ruling; and (2) becomes one with the imposition of sanctions. When it becomes one with the imposition of sanctions, two different relationships are found, namely (1) efforts to encourage accountability for violators; and (2) efforts to distance violators from the process of restoring conditions due to violations that occur.Keywords: General Election, Honorary Council for Election Administration, Ultra Vires. AbstrakPutusan DKPP menjadi instrumen krusial DKPP dalam memutus pelanggaran Kode Etik Penyelenggara Pemilu. Namun, pada perkembangannya ditemukan Putusan DKPP yang melampaui kewenangan (ultra vires). Putusan MK No. 115/PHPU.D-XI/2013 menyatakan Putusan DKPP terbatas pada pelanggaran Kode Etik Penyelenggara Pemilu dan apabila substansi putusan berada di luar ranah a quo, maka Putusan DKPP dinyatakan tidak mengikat dan tidak wajib ditindaklanjuti, serta pembatalan Keputusan Penyelenggara Pemilu karena dianggap cacat hukum. Penelitian ini mencoba untuk melihat eksistensi dan karakteristik Putusan ultra vires DKPP mengingat dampak dari sifat putusan a quo yang cukup signifikan melalui dua rumusan masalah. Pertama, bagaimana eksistensi Putusan ultra vires Dewan Kehormatan Penyelenggara Pemilu? Kedua, bagaimana karakteristik Putusan ultra vires Dewan Kehormatan Penyelenggara Pemilu? Artikel ini merupakan jenis penelitian normatif dengan metode analisis deskriptif-kualitatif. Hasilnya, putusan ultra vires terjadi ketika DKPP memberikan putusan di luar pelanggaran Kode Etik Penyelenggara Pemilu sesuai peraturan perundang-undangan dan masuk pada ranah kewenangan KPU dan Bawaslu. Penulis menemukan 7 Putusan ultra vires DKPP. Terdapat tiga karakteristik dari Putusan ultra vires DKPP, yakni (1) substansi putusan ultra vires terletak pada amar putusan; (2) Putusan ultra vires DKPP memiliki paradigma keadilan restoratif; (3) putusan ultra vires mendorong PTUN untuk menilai kekuatan mengikat Putusan DKPP dan Keputusan tindak lanjutnya. Amar putusan ultra vires pun dituangkan berbeda, yakni (1) berbentuk perintah yang berdiri sendiri; dan (2) menjadi satu dengan penjatuhan sanksi. Ketika menjadi satu dengan penjatuhan sanksi, ditemukan dua relasi berbeda, yakni (1) upaya mendorong pertanggungjawaban pelanggar; dan (2) upaya menjauhkan pelanggar dari proses pemulihan kondisi akibat pelanggaran yang terjadi.Kata Kunci: Dewan Kehormatan Penyelenggara Pemilu, Pemilihan Umum, Ultra Vires.